APPROACHES TO THE PROBLEM OF THE YCHSMA TERRITORY - Díaz Arriola, Luisa (2008)
One of the themes of interest in the archeological study of the Ychsma concerns the territory occupied and administrated by this culture during the Late Intermediate period (1470–1532 AD) and the Late Horizon. Ethno-historical sources limit the Ychsma occupation to the Rimac and Lurín valleys on the central coast, while certain archeological evidences seem to define a larger territory, including the Chilca and the Mala valleys. Although still in analysis, this article develops the problematic of the Ychsma territory with a perspective that considers territory as a space conformed by the cultural homogeneity and diversity. This way we try to choose a different approach to the archeological evidences of the Ychsma and to obtain a dynamic and not static understanding.